Ethical Perspective of Marketing in Czech Republic - Čarný, Tomáš (2021)
The bachelor thesis is focused on the marketing environment in the Czech Republic and its perception by Czech residents from the ethical point of view. Its goal is to evaluate the ethical environment of marketing in the Czech Republic and to suggest possible ways of improvement. The first chapter is devoted to marketing itself and its forms in practice. The second chapter contains an introduction to the issue of ethics in marketing in the Czech Republic and its regulation and operation. The last chapter is focused not only on the research itself using a questionnaire survey, which is quantitatively evaluated using static methods, but also on the evaluation and subsequent recommendations. Residents were found to have a positive attitude towards ethical values. On the other hand, the examined sample show rather negative and skeptical attitude towards marketing practices, and there is therefore a room for improvement in this area by regulation and self-regulation.